The Relationship Between Parenting Styles with Child Empathy: A Bibliometric Analysis - Shinta Shinta; Abd. Madjid (FKIP Universitas Lampung, 2024)
The Relationship Between Parenting Styles with Child Empathy: A Bibliometric Analysis. Objective: This research aims to explore research trends regarding the relationship between parenting styles and empathy for children, as well as describe research development opportunities that can be carried out for further research. Methods: The research method used in this research is descriptive quantitative with a bibliometric approach. The data source was obtained from the Scopus database. The collected data is then exported to a text file in CSV form for further analysis with the help of the Rstudio Package, which includes networking and Biblioshiny visualization. Citation analysis was carried out on data obtained from the database, and then, an overlay was visualized using VOSviewer. Findings: Results show a significant increase in research on the theme from year to year, with a peak in publications in 2021. Valencia and Brigham Young Universities are the main contributors, while the topic of empathy and children's emotional well-being has been a significant focus in recent years. The 2020-2024 period shows several studies that focus on issues regarding parenting styles and also about children's concern for other people. Conclusion: This research concludes that the research theme regarding the relationship between parenting patterns and children's empathy still shows a promising trend. Keywords: bibliometric, child empathy, education, parenting styles.DOI: http://dx.doi.org/10.23960/jpp.v14.i2.202481